METODE PARTISIPATIF DALAM PENGGUNAAN GAWAI DI MADRASAH - Athayla, Sabian; Ramadhana, Rizky Adrian; Amalia, Yasmin; Salma, Syifa; Ardani, Liska; Badru, Irfan Fauzi; Hamdan, Ahmad (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
This article discusses the impact of gadget use on children at Madrasah At-Ta’awun, Tasikmalaya, West Java, with the main focus on preventing excessive gadget use and potential negative effects on children's psychology, learning achievement, and quality of life. Based on the author's community service, the majority of children at Madrasah At-Ta’awun are engaged in religious education through the madrasah, and some of them already have access to gadgets. Gadget usage tends to be focused on entertainment, such as playing games and exploring social media. To address this issue, the author suggests utilizing information technology through instructional videos that explain the dangers of excessive gadget use, preventive measures, and discussion sessions. Rewards in the form of food are given to active participants. This solution plan aims to provide understanding and change children's behavior regarding gadget use at Madrasah At-Ta’awun.